2019
DOI: 10.1038/s41588-018-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

PAX5-driven subtypes of B-progenitor acute lymphoblastic leukemia

Abstract: Recent genomic studies have identified chromosomal rearrangements defining new subtypes of B-progenitor acute lymphoblastic leukemia (B-ALL), however many cases lack a known initiating genetic alteration. Using integrated genomic analysis of 1,988 childhood and adult cases, we describe a revised taxonomy of B-ALL, incorporating 23 subtypes defined by chromosomal rearrangements, sequence mutations, or heterogeneous genomic alterations, many of which show marked variation in prevalence according to age. Two subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
791
6
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(859 citation statements)
references
References 64 publications
32
791
6
7
Order By: Relevance
“…SEM cells infected with the pooled library of sgRNAs were collected at day 0 and day 12 to sequence for sgRNA distribution (Figure 6C). In accordance with prior genome-wide CRISPR screens and functional studies in B-ALL, many survival dependent genes were identified in the top 50 genes in our screen including PAX5 , DOT1L , ZFP64 , YY1 , MEF2C , MYC and KMT2A (26, 29, 50, 51). USF2 was ranked as the top 24 th essential gene in MLLr SEM cells (Figure 6D).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…SEM cells infected with the pooled library of sgRNAs were collected at day 0 and day 12 to sequence for sgRNA distribution (Figure 6C). In accordance with prior genome-wide CRISPR screens and functional studies in B-ALL, many survival dependent genes were identified in the top 50 genes in our screen including PAX5 , DOT1L , ZFP64 , YY1 , MEF2C , MYC and KMT2A (26, 29, 50, 51). USF2 was ranked as the top 24 th essential gene in MLLr SEM cells (Figure 6D).…”
Section: Resultssupporting
confidence: 83%
“…As shown by many previous studies, HOXA9 overexpression was observed in refractory MLL-rearranged ALL and AML patients (2628)(Figures S1A-S1C). Therefore, we utilized our previously reported high-efficiency knock-in strategy, “CHASE knock-in” (29), to deliver the P2A-mCherry cassette upstream of the HOXA9 stop codon in a patient-derived human B-ALL cell line, SEM, which has a typical B-ALL signature along with a t(4;11) translocation and maintains one single allele of the HOXA gene cluster.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Although various PAX5 alterations, including fusions, amplifications, or mutations, were detected in BCP-ALL, the expression profiles of these samples were similar regardless of PAX5 alterations without PAX5 deletions. 23 In our cohort, our defined PAX5-altered samples were also clustered into the single cluster, E3, although our sample size was small and our analysis might not be precise. Because PAX5 deleted samples were not necessarily clustered into E3 and were detected in 4 clusters, PAX5 deletion would have different pathogenicity from other PAX5 alterations.…”
Section: Mutation and Copy Number Analysismentioning
confidence: 89%
“…In childhood ALL the initiating event occurs most commonly in-utero and consists usually of an aberration of a transcriptional regulator. Progression to leukemia is caused by a series of acquired genetic aberrations that halt B-cell differentiation and increase cell proliferation, survival and self-renewal 2,3 . Increased signaling through RAS or STAT5 pathways are typical progression events and are generally thought to act as the "fuel" enhancing leukemic cell growth [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%